2002
DOI: 10.1097/00005131-200205000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Fixation of Tibial Plateau Fractures

Abstract: It is logical to define failure of fixation using the same measures considered as indications for reduction and fixation. Using these strict criteria, the incidence of radiologic failure was much higher than previous published series. In the elderly this was unacceptably high, and treatment goals should be limited to restoring stability and alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 27 publications
4
76
0
5
Order By: Relevance
“…52 Furthermore, restricted weight-bearing may be impractical, and many of these patients will walk fully weight-bearing regardless of the instructions given. 45 Therefore, we elected to allow our patients to start weight-bearing at three weeks and alignment was maintained in most of them. If, however, loss of reduction does occur, an important advantage of using the ring external fixation is the ability to carry out an early corrective osteotomy with the frame still in place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Furthermore, restricted weight-bearing may be impractical, and many of these patients will walk fully weight-bearing regardless of the instructions given. 45 Therefore, we elected to allow our patients to start weight-bearing at three weeks and alignment was maintained in most of them. If, however, loss of reduction does occur, an important advantage of using the ring external fixation is the ability to carry out an early corrective osteotomy with the frame still in place.…”
Section: Discussionmentioning
confidence: 99%
“…45 Long-film radiographs for assessment of the mechanical axis of the limb were taken and compared with those of the contralateral normal limb in order to measure malalignment. Post-traumatic osteoarthritis (OA) was assessed on the most recent radiograph, on the basis of narrowing of the joint space, subchondral sclerosis, cysts and osteophytes.…”
Section: Methodsmentioning
confidence: 99%
“…Both external fi xation and dual plating were sensitive to the bone quality with all failures due to cut-out within the bone [ 37 ] . Age and poor bone quality are associated with higher failures of fi xation in the treatment of tibial plateau fractures [ 38 ] . Some authors are advocating ORIF with dual plates and supplemental external fi xation post-operatively to avoid fi xation failures in this geriatric patient population [ 39 ] .…”
Section: Spanning External Fixation and Delayed Open Reduction And Inmentioning
confidence: 99%
“…10 This reduction in BMD results in an increased risk of re-displacement of fractures, which may be as high as 79% in patients over the age of 60. 11 While several studies have reported promising results with the use of circular external fixation, little data is available on its use in the elderly. 1,2,8 In the elderly hybrid external fixation has been reported to deliver inferior results in comparison to internal fixation.…”
Section: Introductionmentioning
confidence: 99%